Evaluasi Sistem Pengelolaan Sampah Berkelanjutan di Universitas Muhammadiyah Malang: Analisis Perilaku dan Persepsi Civitas Akademika - Samin, Samin (Mahesa Research Center, 2026)
Sustainable waste management on campus requires active participation from the academic community. This study aimed to analyze waste disposal and sorting practices and their relationship with perceptions of waste management systems, adequacy of waste bin facilities, and environmental education at Universitas Muhammadiyah Malang (UMM). A survey method was employed using questionnaires distributed to 116 respondents, including students, lecturers, and staff. Data were analyzed using descriptive statistics, Chi-square tests to examine associations, and Spearman correlation to assess relationships between sorting behavior and perceptions. The results showed that compliance with proper waste disposal was high, with more than 80% of lecturers reporting consistent behavior. However, waste sorting practices remained low (30–35%). Most respondents perceived the waste management system and bin availability as adequate, although lecturers and staff were more critical regarding environmental education and facilities. Chi-square analysis revealed significant associations between respondent groups and both behavior and perception variables, while Spearman correlation indicated a weak positive relationship between waste sorting behavior and perceptions of facilities and environmental education. These findings highlight the need to improve facilities and strengthen environmental education to promote more effective waste sorting practices on campus.